Application of ICTs to Achieve Inclusion of all Farmers under Kisan Credit Cards in Indian Agriculture - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
Institutional Credit is an especially important input in Indian Agriculture. Kisan Credit Cards (KCC) have emerged as the instrument of choice to advance formal credit to Indian farmers. Government of India has undertaken 2 campaigns since February 2019 to saturate the number of KCCs. We analysed these campaigns and find that the net effect of these campaigns is absent altogether on the ground with respect to the number of KCCs. We suggest an alternative approach to include all farmers, particularly the landless cultivators (tenants, sharecroppers, oral lessees etc.) within the ambit of KCC so that saturation is achieved in a true and inclusive sense. The exercise can also yield robust estimates on the extent and terms of tenancy, which can be used to further fine-tune agriculture policy in India.
Keywords: 330